Studying temporal variability of GRS 1739-278 during the 2014 outburst - Ilya A. Mereminskiy; Andrey N. Semena; Sergey D. Bykov; Ekaterina V. Filippova; Alexander A. Lutovinov; Juri Poutanen (OXFORD UNIV PRESS, 2022)
We report a discovery of low-frequency quasi-periodic oscillation at 0.3-0.7 Hz in the power spectra of the accreting black hole GRS 1739-278 in the hard-intermediate state during its 2014 outburst based on the NuSTAR and Swift/XRT data. The QPO frequency strongly evolved with the source flux during the NuSTAR observation. The source spectrum became softer with rising QPO frequency and simultaneous increasing of the power-law index and decreasing of the cut-off energy. In the power spectrum, a prominent harmonic is clearly seen together with the main QPO peak. The fluxes in the soft and the hard X-ray bands are coherent, however, the coherence drops for the energy bands separated by larger gaps. The phase lags are generally positive (hard) in the 0.1-3 Hz frequency range, and negative below 0.1 Hz. The accretion disc inner radius estimated with the relativistic reflection spectral model appears to be R-in < 7.3R(g). In the framework of the relativistic precession model, in order to satisfy the constraints from the observed QPO frequency and the accretion disc truncation radius, a massive black hole with M-BH a parts per thousand 100 M-aS (TM) is required.